PENGARUH PENERAPAN CORPORATE SOCIAL RESPONBILITYTERHADAP CITRA PERUSAHAAN PT TIRTA INVESTAMA KEBONCANDI PADA MASYARAKAT DESA JELADRI WINONGAN PASURUAN - Murtadlo, Kholid (SKeTsa Bisnis (e-jurnal), 2014)
Abstract Corporate image is how the public receives external communications effort through an organization that serve as the public response to the overall offering by the company and is defined as the number of beliefs, ideas and the public image of a company / organization. Variabel in this study is X1 (Community Support), X2 (Environment), X3 (Product) and Y (Corporate Image). Framework in partial allegedly having an X1 to variabel Y, while the X2 variabel also affects the variabel Y and variabel X3 dominant influence on the variable Y. The research results of logit regression analysis is, for variabel X1 (Community Support) Î² by 0843 while 9,041 Wald and Probability for 0003 amounted to 2,323 Exp.Î² with significant results. For the variabel X2 (Environment) of 0.542 whereas Î² Wald 7216 and 0007 amounted to Exp.Î² probability of 1.720 with significant results. For variabel X3 (Product) by 0526 whereas Î² Wald 4,131 and Probability for 0042 amounted to 1,692 Exp.Î² with significant results. Corporate Social Responsibility is a social responsibility by companies / organizations on what has been done by the company / organization in the form of activities that will have an impact on the environment, especially to the possibility of environmental damage getting worse. From the above definition it is clear that CSR greatly affect the image of a company. Basically the judge said the company is good or bad can be seen through the provision set forth, for the community or the public may not give a good impression without knowing assistance as outlined by the company.